Research and Build for Remote Pair Programming for Learning - Dodson, Anna (2016)
This project researches the positive effects of pair programming and collaborative learning and aims to prove pair programming remotely is successful to learning. A pair programming web application was built to test this. The application was designed for a driver and navigator to chat and learn together with only the driver being able to write the code. User studies were carried out on the build to attempt to determine the positive affects of pair programming and if any evidence to support switching roles after a set period of time to benefit learning could be found. User studies provided results that showed evidence of successful pair programming which would support learning.